Epigenetic Mechanisms Leading to Overexpression of HMGA Proteins in Human Pituitary Adenomas - D’Angelo, Daniela; Esposito, Francesco; Fusco, Alfredo (Frontiers in Medicine, 2015)
Overexpression of the HMGA1 and HMGA2 proteins is a feature of all human pituitary adenoma subtypes. However, amplification and/or rearrangement of the HMGA2 have been described in human prolactinomas, but rarely in other pituitary subtypes, and no genomic amplification of HMGA1 was detected in pituitary adenomas. Here, we summarize the functional role of HMGA proteins in pituitary tumorigenesis and the epigenetic mechanisms contributing to HMGA overexpression in these tumors focusing on recent studies indicating a critical role of non coding RNAs in modulating HMGA protein levels.